Socio-Economic Role of Infrastructure Projects in the Spatial Development of the Volga Federal District - Korchagina, Julia Stanislavovna (International Journal of Criminology and Sociology, 2022)
The article is devoted to assessing the role of infrastructure projects in the spatial development of the Volga Federal District. First of all, the regions of the Volga Federal District were ranked by the factor of financing infrastructure projects. Then, regression dependencies of this factor with socio-economic indicators of the constituent entities development were identified. In addition, a map was developed reflecting the spatial differentiation of the Volga Federal District regions on the development of infrastructure projects.